PENGEMBANGAN E-LKPD BERBASIS GOOGLE SITES MATERI KERAGAMAN KEBUDAYAAN UNTUK MENINGKATKAN SELF EFFICACY SISWA KELAS IV SEKOLAH DASAR - Kurotul, Anjelika; Alfi, Cindya; Fatih, Mohamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was carried out as one of the efforts to achieve maximum learning, especially in learning that teachers and students felt experienced obstacles. This effort was carried out by developing electronic learning media, student worksheet based on Google Sites, materializing cultural diversity in Class IV elementary school students with the aim of increasing students' self-efficacy. This research uses the R&D method with the Borg and Gall development model. The instrument used for data collection was a product validity questionnaire, product feasibility and questionnaires to increase student self-efficacy. Product validity results were obtained through assessments by media experts with a percentage of 85.4%, material experts 92.5%, and language experts 75.5%. The results of the feasibility test were assessed by the teacher with a percentage of 95% in the category, very feasible. The results of increasing student self-efficacy were obtained through a response questionnaire, students with an N-Gain value of 0.81 in the high category. Based on the data obtained, the Google-based electronic student worksheet cultural diversity material sites have been proven to increase the self-efficacy of fourth grade students and are suitable for use.